2013
DOI: 10.1111/head.12271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Frequency and the Association of Sexual Pain and Chronic Headaches

Abstract: Chronic headaches and sexual pain are both conditions that have a significant impact on patients and the health care system, and they do coexist. More research is needed to look at the relationship between these conditions in addition to epidemiology, symptomatology, evaluation, and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Consistent with the literature ( Ghizzani et al, 2014 ; Granero-Molina et al, 2023 ), high levels were also found in FM and CO (which also includes comorbidities of FM and VU conditions). The percentage of pain in the CH group is comparable to that found by Gordon et al (2014) (39 % vs 44 %), while that presented by the control group is similar to that reported by an earlier Italian study on the general population ( Nimbi et al, 2020 ), that still remains high and worthy of attention. Regarding sexuality, as well explained by Basson's circular sexual response model ( Basson, 2000 ), when pain becomes intertwined with the sexual response, it can detrimentally impact not only the entire sexual experience, but also psychological, relational, and social aspects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the literature ( Ghizzani et al, 2014 ; Granero-Molina et al, 2023 ), high levels were also found in FM and CO (which also includes comorbidities of FM and VU conditions). The percentage of pain in the CH group is comparable to that found by Gordon et al (2014) (39 % vs 44 %), while that presented by the control group is similar to that reported by an earlier Italian study on the general population ( Nimbi et al, 2020 ), that still remains high and worthy of attention. Regarding sexuality, as well explained by Basson's circular sexual response model ( Basson, 2000 ), when pain becomes intertwined with the sexual response, it can detrimentally impact not only the entire sexual experience, but also psychological, relational, and social aspects.…”
Section: Discussionsupporting
confidence: 87%
“…Our hypotheses were that each group would show a similar situation of impairment concerning sexual experience, with peculiarities. For example, we expect to find higher levels of genito-pelvic pain and impairment of sexual functioning in VU, FM and CO groups in line with the literature ( Casale et al, 2021 ; Chisari et al, 2021 ; Collado-Mateo et al, 2020 ; Nimbi et al, 2020 ; Ricoy-Cano et al, 2022 ), significantly different from CH and HC ( Gordon et al, 2014 ; Nappi et al, 2012 ; Nimbi et al, 2020 ).…”
Section: Aimssupporting
confidence: 78%
“…These conditions included chronic pelvic pain, chronic low back pain, chronic headache, or fibromyalgia. Multiple studies have demonstrated that patients with other chronic pain conditions are more likely to develop chronic pelvic pain in general (8-11). The timing of the development of pain and the strength of the association suggests that those with chronic pain syndromes may be predisposed to the development of pain after hysteroscopic sterilization with Essure™.…”
Section: Discussionmentioning
confidence: 99%